The Potential of Orthotropic Branch Number to Enhance the Yield of Pepper (Piper nigrum L.) Grown on Dead Poles - Sitti Nurul Aini; Ani Kurniawati; Didy Sopandie; Hariyadi Hariyadi; Sudirman Yahya (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2026)
Bangka Belitung, as the largest pepper production center in Indonesia, is experiencing indications of a decline in pepper productivity due to the traditional cultivation system, such as depending on chemical fertilizer, using dead poles, and without a cover crop. Increasing pepper yield can be achieved by increasing the number of orthotropic branches per plant. This research aimed to investigate pepper potential yield by varying the number of orthotropic branches. This research was conducted in Perlang Village, Indonesia, and took time between March 2023 and August 2024, employing a non-factorial Completely Randomized Design (CRD). The treatments consist of: R1 (3 branches), R2 (4 branches), R3 (5 branches), and R4 (6 branches). The results indicated that the branch number treatment did not affect microclimate beneath the pepper canopy or pepper leaf morphology. Furthermore, the branch number treatment did not affect plant physiological activity, yield components, or white pepper quality. Piperine content ranged from 5.22 to 6.29, essential oil from 2.21 to 2.41, and no statistically significant differences were observed among treatments. However, increasing the number of branches has the potential to enhance pepper yield by increasing the number of panicle/plant. Six orthotrophic branches/plant have the potential to increase pepper yield, cultivated using dead poles. Having six orthotrophic branches per plant does not negatively impact the quality and quantity of the white pepper produced.